RECENT WIKI SYSTEMS IN EDUCATION - SLABÝ, Jiří (Trends in education, 2008)
The contribution deals with recent wiki systems, which are one of education tools in Web 2.0 solution. These systems could be efficient tools for students' collaboration in education and it also could increases students' engagement and participation. Concept of Web 2.0 is mentioned. These recent wiki systems are demonstrated on Google Sites (Goole Apps), which is one of the few localized nowadays in Czech.
Keywords: wiki; information sharing; collaborative tools; Web 2.0; Goggle Apps